2022
DOI: 10.3389/fphys.2022.838479
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Lung Ultrasound in Aortic Stenosis

Abstract: Background: Aortic stenosis (AS) is the most common primary valve lesion requiring intervention in Europe and North America. It has a prolonged subclinical period during which, as AS worsens, left ventricular adaptation becomes inadequate and impaired systolic and/or diastolic dysfunction may lead to overt heart failure (HF). The development of HF is an inflexion point in the natural history of AS. Pulmonary congestion is a cardinal feature in HF, and lung ultrasound (LUS) evaluation of B-lines has been propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This comet-tail artifact can be correlated to several clinical conditions, such as pulmonary edema, ARDS, chronic interstitial diseases, as well as focally with infectious or ischemic processes [ 30 , 57 , 58 , 59 ]. For aortic stenosis, it was shown that the number of B-lines correlates with the hemodynamic changes caused by the valve lesion and the functional status of the patient [ 60 ].…”
Section: Lung Sonography Signs Patterns and Clinical Interpretationmentioning
confidence: 99%
“…This comet-tail artifact can be correlated to several clinical conditions, such as pulmonary edema, ARDS, chronic interstitial diseases, as well as focally with infectious or ischemic processes [ 30 , 57 , 58 , 59 ]. For aortic stenosis, it was shown that the number of B-lines correlates with the hemodynamic changes caused by the valve lesion and the functional status of the patient [ 60 ].…”
Section: Lung Sonography Signs Patterns and Clinical Interpretationmentioning
confidence: 99%
“…Furthermore, compared to controls, ultrasound signs of pulmonary (B-lines) and systemic congestion (inferior vena cava [IVC] diameter and RVF pattern) are increased in ASpEF as much as in HFpEF. While it has already been shown that the number of B-lines and a dilated IVC correlate with deranged haemodynamics and increased risk of adverse events in AS, 33,34 this is the first study to comprehensively investigate multi-organ congestion in ASpEF. Such alterations also translate into ventilatory impairment, expressed by more severe ventilation-perfusion mismatch and ventilatory inefficiency.…”
Section: Cardiovascular Function and Exercise Capacitymentioning
confidence: 93%
“…ESE can also highlight signs of dynamic increases in sPAP and pulmonary congestion (LUS B-lines) during the whole exercise, which carry an adverse prognostic significance in AS. 61 At the same time, CPET can indirectly assess SV response (VO 2 /work slope) and correlate echographic evidence of pulmonary congestion with data regarding ventilation/perfusion mismatch (VE/VCO 2 slope).…”
Section: Cpet-ese In Specific Conditionsmentioning
confidence: 99%